Effect of Peeling and Cooking on Nutrients in Vegetables - Alvi, Shahnaz; Khan, K.M.; Sheikh, Munir A.; Shahid, Muhammad (Pakistan Journal of Nutrition, 2003)
Four vegetables brinjal, bitter gourd, colocasia and tomato were subjected for total protein, crude fiber, ash calcium, magnesium, phosphorus, potassium, ascorbic acid and folic acid contents in raw peeled raw cooked and peeled cooked forms. Losses of nutrients due to peeling and cooking were determined. The loss of protein was non-significant during peeling and was significant during cooking except in colocasia. Vegetables lost crude fiber significantly during peeling, cooking caused significant effect only in peeled form, ash reduced significantly during peeling and cooking except in tomato. Four minerals reduced significantly in both peeling and cooking especially in peeled cooking. Vitamins losses were highly significant in both peeling and cooking.